2022
DOI: 10.3389/fnagi.2022.891202
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Decline of Speech Perception

Abstract: Hearing loss is one of the most common disorders worldwide. It affects communicative abilities in all age groups. However, it is well known that elderly people suffer more frequently from hearing loss. Two different model approaches were employed: A generalised linear model and a random forest regression model were used to quantify the relationship between pure-tone hearing loss, age, and speech perception. Both models were applied to a large clinical data set of 19,801 ears, covering all degrees of hearing lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
1
6
0
1
Order By: Relevance
“…This suggested that speech perception abilities of older adults even with normal hearing threshold tended to gradually decrease with aging. Age-related decline in speech perception was also reported in previous studies (Goossens et al, 2017;Hoppe et al, 2022), and prior neuroimaging research has revealed that age-related neural disruption may be a hallmark of these speech processing difficulties (Irsik et al, 2021;Tremblay et al, 2021).…”
Section: Speech Perception Task Performancesupporting
confidence: 65%
“…This suggested that speech perception abilities of older adults even with normal hearing threshold tended to gradually decrease with aging. Age-related decline in speech perception was also reported in previous studies (Goossens et al, 2017;Hoppe et al, 2022), and prior neuroimaging research has revealed that age-related neural disruption may be a hallmark of these speech processing difficulties (Irsik et al, 2021;Tremblay et al, 2021).…”
Section: Speech Perception Task Performancesupporting
confidence: 65%
“…In the previous study [ 14 ], the inclusion criterion was limited to cases with a hearing loss of 80 dB HL or less. In this group, the WRS max is usually greater than zero [ 15 ]. For candidates with a hearing loss greater than 80 dB HL , a WRS max better than zero was observed for 44 of 82 cases (54%).…”
Section: Discussionmentioning
confidence: 99%
“…The first significant deficits were observed in normal-hearing participants between the ages of 40 and 49 years, even in the absence of peripheral hearing loss. Above the age of 40 years, the maximum word recognition score also starts to decline, as observed in a large cohort [ 27 ].…”
Section: Introductionmentioning
confidence: 94%